TINJAUAN YURIDIS TERHADAP PEMBERIAN KREDIT BANK DENGAN JAMINAN PERSONAL GUARANTEE (Study Pada Bank BRI Cabang KCP Willem Iskandar) - Kennie Dhillon (JURNAL CIVIL LAW USU, 2013)
Abstract : Banks play an important role in serving the community. The process of credit with Bank BRI branch KCP Willem Alexander, among others: The entire entry will be submitted in writing by the customer / prospective borrowers who file signed by the authorized officials. Letter of request through the "Customer Service" presented to "the Business Unit" as the customer. "Bussines Unit 'clients examine the request for approval is feasible or not. "Bussines Unit" assess the applicant's reputation and business prospects are good, then "the Business Unit" recommendations to "Credit Risk" in the form of Memorandum Management Area. And evaluate the proposed credit facility and represent it in the form of "Credit Report". What if the loan application can be approved then the next "Credit Risk" Management Area signed the "Credit Approval" together with "the Business Unit" on "level of authority" the same. "Bussines Unit" to create and submit a notice with the approval given to customer with a copy submitted to the Credit Risk Management to prepare the credit agreement. With the guarantee that there are no barriers constraints sebagimana in general .The right of an insurer to not be bound together with the debtor bears responsibility. The right to file a rebuttal sipenjamin.Rights sipenjamin to divide debt.Rights sipenjamin to be dismissed from the guarantor. Liability insurance can switch to an heir, and are subside.    Kata Kunci : Kredit, Bank, Personal Guarantee.